신규간호사의 회복탄력성와 임상수행능력 관계에서 간호조직문화의 조절효과 - 이한나(Lee, Hanna); 박은준(Park, Eun-Jun) (Kanho Haengjŏng Hakhoe chi = The journal of Korean Nursing Administration Academic Society, 2024)
연구목적: 신규간호사의 회복탄력성과 임상수행능력 관계에서 간호조직문화의 조절효과를 파악하기 위함이다. 연구방법: 서울, 경기도에 위치한 세 개 종합병원에서 3~12개월 경력의 신규간호사를 대상으로 2023년 3월 14일부터 7월 14일까지 설문조사를 실시하였다. 총 193명의 응답 자료를 이용해 기술통계, 상관관계분석, 위계적 회귀분석을 실시하였다. 연구결과: 신규간호사의 회복탄력성은 ‘보통 수준’으로 나타났고 임상수행능력은 ‘좋은 수준’으로 나타났다. 신규간호사는 위계지향문화, 관계지향문화, 혁신지향문화, 업무지향문화 순으로 높게 인식하고 있었다. 임상수행능력은 회복탄력성이 높을수록(β=.40, p<.001), 위계지향문화를 강하게 인식할수록(β=.16, p=.013) 높았다. 회복탄력성과 혁신지향문화의 상호작용(β=.22, p=.012)이 통계적으로 유의하였고, 이를 통해 혁신지향문화를 높게 인식할 때 회복탄력성이 임상수행능력에 미치는 영향이 더 크다는 것을 확인하였다. 결론: 신규간호사의 임상수행능력을 향상시키기 위해서는 개인의 회복탄력성을 강화하고, 조직 차원에서는 위계지향문화의 긍정적인 측면과 함께 혁신지향문화를 강화하는 것이 중요하다. Purpose: This study aims to identify the moderating effect of nursing organizational culture on the relationship between resilience and clinical competence among new graduate nurses. Methods: A survey was conducted from March 14 to July 14, 2023, targeting 210 new nurses with 3 to 12 months of experience, working in three general hospitals in Seoul and Gyeonggi-do. Data from 193 respondents were analyzed using descriptive statistics, correlation, and hierarchical regression. Results: The resilience of new graduate nurses was moderate and their clinical competence was rated as good. They perceived a strong hierarchy-oriented culture, followed by a relationship-oriented culture, an innovation-oriented culture, and lastly, a task-oriented culture. Clinical competence was higher with greater resilience (β=.40, p<.001) and stronger perception of hierarchy-oriented culture (β=.16, p=.013). The interaction between resilience and innovation-oriented culture (β=.22, p=.012) was statistically significant, indicating that the effect of resilience on clinical competence was significantly higher when the innovation-oriented culture was strongly perceived. Conclusion: To improve the clinical competence of new graduate nurses, it is essential to enhance their personal resilience and, at an organizational level, to strengthen the positive aspects of hierarchy-oriented and innovation-oriented cultures. KCI Citation Count: 0